The investigation of lipid peroxidation, anti-oxidant levels and some hematological parameters in sheep naturally infested with Wohlfahrtia magnifica larvae - Ipek, Duygu Neval Sayin; Saki, Cem Ecmel; Cay, Mehmet (Elsevier Science Bv, 2012)
Wohlfahrtia magnifica is the main agent of traumatic myiasis in many central and eastern European countries as well as in the Mediterranean basin and Asian countries. The present study was aimed to investigate the effect of myiasis infestation on lipid peroxidation, antioxidant levels and several hematological parameters in the sheep naturally infested with W. magnifica larvae. A total of 38 sheep, including 19 awassi sheep naturally infested with W. magmfica larvae and 19 clinically healthy awassi sheep, were studied. The infected animals were divided into three groups depending on the number of larvae (Group 1: <50 larvae: Group 2: 50-100 larvae; Group 3: >100 larvae). In blood samples, red blood cell counts, hemoglobin, hematocrit concentration and white blood cell, neutrophil, lymphocyte, eosinophil, basophil counts, plasma malondialdehyde, erythrocyte glutathione levels and erythrocyte glutathione peroxidase activity were studied. The results revealed a marked decrease in red blood cell counts and hemoglobin concentrations along with a significant increase in white blood cell and neutrophil counts. The elevation in plasma malondialdehyde levels, a function of lipid peroxidation, established a significant difference between the control group and groups 2, 3. Decreased activity of erythrocyte glutathione peroxidase was found significant in the control group and all parasitemia. We conclude that in natural infestations with W. magnifica, as in infestation with Lucilia cuprina, there is a notable increase in inflammatory activities resulting from the movements, secretions, and toxins of the larvae and form the toxins secreted by the bacteria - which leads to an impression of anemia - and that the tissue injury results in an increase in level of free radicals in the organism. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Wohlfahrtia magnifica; Antioxidants; MDA; Hematological parameters; Sheep